COMMUNITY PARTICIPATION AND HUMAN RIGHTS EDUCATION- PROSPECTS AND PROBLEMS IN KANO STATE - Hassan, Mohammad S.B. (Sokoto Educational Review, 2011)
A higher level of community participation has been for long advocated in social activities in Nigeria, especially among local communities who are not only unserved but in social disadvantage. This discussion provides not only a justification for community participation in ensuring social rights for the benefit of all citizens but also argues that only through this means can the quality of life for the average Nigerian, and residents of Kano State, in particular, be improved. The paper also makes the case that Nigeria is a society where the human rights of the people are commonly infringed and strongly suggests that Governmental neglect of the needs of people is a risk that promises no leader any future good. Thus, community participation appears to be a ’double-edged sword’ that is bound to increase if only to intensify the self-serving characteristic that Democracy endows upon the citizenry in the quest for a more satisfactory livelihood. The Nigerian Elite should therefore realize that True Democracy, which is evident in community participation, is but a mere illusion when pursued short of a massive involvement of the citizenry in all social affairs, including the elite s’ own access to power.